Time-resolved CARS measurements of vibrational decoherence of I2 isolated in matrix Ar: Spectroscopy in Cryocrystals and Matrices - Karavitis, M.; Segale, D.; Bihary, Z.; Pettersson, M.; Apkarian, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Time-resolved coherent anti-Stokes Raman scattering is applied to prepare and interrogate vibrational coherences on the ground electronic surface of molecular iodine isolated in Ar matrices. The coherence decay time shows a linear dependence on vibrational quantum numbers, for v = 3–15. The temperature dependence of decoherence rates is negligible for v < 7, in the experimental range T = 18–32 K. For a v = 13, 14 superposition, the temperature dependence indicates dephasing by a 66 cm–1 pseudo-local phonon, just outside the Debye edge of the solid. The accuracy of the data is limited due to two-photon induced dissociation of the molecule, which process is characterized using polarized fields. The T → 0 limit of dephasing is discussed.